Transcriptional regulation of Drosophila gonad formation - Tripathy, Ratna; Kunwar, Prabhat S.; Sano, Hiroko; Renault, Andrew D. (Elsevier, 2014)
The formation of the Drosophila embryonic gonad, involving the fusion of clusters of somatic gonadal precursor cells (SGPs) and their ensheathment of germ cells, provides a simple and genetically tractable model for the interplay between cells during organ formation. In a screen for mutants affecting gonad formation we identified a SGP cell autonomous role for Midline (Mid) and Longitudinals lacking (Lola). These transcriptional factors are required for multiple aspects of SGP behaviour including SGP cluster fusion, germ cell ensheathment and gonad compaction.